DEVELOPMENT OF INTERACTIVE LEARNING MEDIA FOR THE BASICS OF ELECTRICAL ENGINEERING BASED ON AUGMENTED REALITY - Muhammad Iqbal Nugraha; Irwanto Irwanto; Desmira Desmira (EDUPROXIMA : Jurnal Ilmiah Pendidikan IPA, 2024)
The purpose of this study is to clarify the development process of interactive learning media for the fundamentals of electrical engineering based on Augmented Reallity (AR) and to assess the feasibility of AR-based interactive learning media to help students of Class X to understand the content related for the basics of electrical engineering at vocational high schools. This study use methodology Research and Development, specifically Waterfall model (2010). The research subjects consisted of five lecturers and one teacher. Data collection methods included both tests and non-tests. The interactive learning media trials yielded positive results for the development of AR-based electricity engineering as a teaching material. The average overall score given by media experts was 48 in range of ???? ≥ 42 it is the 'Very Appropriate' category. The material experts gave an overall aspect score of 21,333 on average, with a range of ???? ≥ 18 it is 'Very Appropriate' category. The average overall score of student respond to AR-based learning media was 40,655 on average, with a range of ???? ≥ 36 in the 'Very Appropriate' category.